MICOTOXINAS NA ALIMENTAÇÃO DO GADO LEITEIRO DA REGIÃO METROPOLITANA DE CURITIBA: UM (DES)CONHECIMENTO QUE FAZ DIFERENÇA - Coimbra, Lia Suzana Guimarães (Scientia Agraria, 2003)
The present work aimed at obtaining information about the level of knowledge that milk producers in the greater Curitiba milk belt had about the presence of mycotoxins in feedstuff given to dairy cows. The work also aimed at verifying the orientation given to dairy farmers, and the role governmental institutions played in the control of milk contamination, with its known impact on human and animal health as well as on social and economic grounds. Methodological strategy has been based on quality appraisal using interviews as the process of data collection. Interviews have been conducted with twelve milk producers from either small, medium or large farms. Technicians from both private and Government Institutions were also questioned about the specific legislation on the issue. When analysing end results. one comes to the conclusion that dairy farmers are unaware of the existence of mycotoxins and their consequences. It has also been observed that there is no efficient inspection and / or control from government agencies. It is, therefore, incumbent on government officials, area-related professionals and the universities the task to take this issue and discuss it with the milk producers. making sure adequate prophylaxis can be applied.